Being real: the student-teacher relationship and African-American male delinquency - Gibson, Camille (Criminal justice, 2002)
Cause for concern -- What we know -- A researcher investigates -- The social, political, and economic contexts -- The school players -- Student-teacher interactions -- Student outcomes -- What's to be done.